Amyloid-beta 25-35 peptide induces expression of monoamine oxidase B in cultured rat astrocytes - Song Wei; Zhou Li-Jun; Zheng Shi-Xi; Zhu Xing-Zu (Acta Pharmacologica Sinica, 2016)
"AIM: To investigate the effects of amyloid-beta 25-35 peptide (A beta 25-35) on monoamine oxidase (MAO) expression and activity in primary cultured rat astrocytes. METHODS: Immunocytochemistry was used to observe the morphological changes in astrocytes. Fluorescence spectrophotometry was used to measure the activity of MAO in astrocytes. The expression of MAO in astrocytes was assayed by RT-PCR. RESULTS: A beta 25-35 induced a reactive morphological change in cultured rat astrocytes which was accompanied by increased immunoreactivities for glial fibrillary acidic protein. Treatment with A beta 25-35 resulted in an elevation of MAO activity in a dose- and time-dependent manner. A beta 25-35-induced enhancement of MAO activity was of type B (MAO-B). The increase in MAO-B activity appeared to be due to an increase in the number of enzyme molecules since kinetic analysis demonstrated a 1.5 fold increase in Vmax with no change in Km. Treatment with A beta 25-35 also led to a substantial increase in MAO-B mRNA level in the astrocytes. CONCLUSION: A beta 25-35 is able to selectively induce MAO-B expression in rat astrocytes and that the upregulation of MAO-B in A beta 25-35-stimulated astrocytes may play an important role in the pathogenesis of Alzheimer's disease."